The Structure of OECD Unemployment - Collins, Taylor (Journal of Applied Business and Economics, 2021)
In this paper, I apply a set of unit root tests on 31 OECD countries in order to uncover evidence on the best way to model their unemployment rates. There are three primary classes of theories into how the unemployment rate evolves (natural rate theories, hysteresis theories, and structural theories) and they each have very distinct statistical properties related to unemployment persistence. In this paper, I use a set of Markov-Switching Augmented Dickey Fuller tests to find evidence that 20 of the 31 countries could be better modeled by structuralist theories of unemployment than by hysteresis theories or natural rate of unemployment theories. These results provide comparable evidence supporting structural theories of unemployment to previous papers that have used different sets of unit root testing techniques.